Pengaruh Penggunaan Chatbot Dalam Customer Service Terhadap Loyalitas Pelanggan Pada Perusahaan Telkomsel - Fithri Wulandari; Didi Ahdiat; Sudrajat; Hanifatul Riskiyai; Faedah Nuryaningsyih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Current technological developments create new media so that humans can communicate with chatbots to meet their need for information. All customer needs, starting from submitting customer complaints to accessing services, can be done quickly using chatbots. Indonesia has several large companies that have adopted chatbots to make it easier for customers to get customer service on a self-service basis or without human assistance. This study aims to analyze the effect of using chatbots in customer service on customer loyalty at Telkomsel companies. This study uses quantitative methods with survey methods. The results of the study show that the customer experience using chatbots is significantly influenced by perceived usefulness when interacting with Veronika's chatbots. Chatbot has a significant influence on customer satisfaction and loyalty in using Telkomsel services.